Calf muscle strain injuries in elite Australian Football players: A descriptive epidemiological evaluation. (8th October 2019) - Green, Brady; Lin, Monica; Schache, Anthony G.; McClelland, Jodie A.; Semciw, Adam I.; Rotstein, Andrew; Cook, Jill; Pizzari, Tania
Abstract : Background: Calf muscle strain injuries (CMSI) show consistent rates of prevalence and re‐injury in elite Australian Football players. An epidemiological evaluation is warranted to better understand the clinical presentation and recovery of CMSI. Purpose: First, to describe the epidemiology of CMSI in elite Australian Football players. Second, to determine if recovery following injury is different according to: (a) injury type (index vs re‐injury); (b) muscle injured (soleus vs gastrocnemius); and (c) mechanism of injury (running‐related activity vs non running‐related activity). Study design: Descriptive epidemiological. Methods: Data retrieved from the Soft Tissue injury Registry of the Australian Football League were analyzed. Sixteen clubs submitted data on CMSI from 2014 to 2017. Data included: player characteristics, training and match history at the time of injury, MRI, and the time to reach recovery milestones. Results: One hundred and eighty‐four CMSI were included (149 index injuries; 35 re‐injuries). Soleus injuries were most prevalent (84.6%). Soleus injuries took 25.4 ± 16.2 days to return to play, whereas gastrocnemius injuries took 19.1 ± 14.1 days ( P = .097). CMSI sustained during running‐related activities took approximately 12 days longer to recover than injuries sustained during non running‐related activities ( P = .001). Compared to index injuries, re‐injuries involved older players ( P = .03) and significantly more time was taken to run at >90% of maximum speed, return to full training, and return to play ( P ≤ .001). Almost all of the observed re‐injuries involved soleus (91.4%). Conclusion: Soleus injuries are more prevalent than gastrocnemius injuries in elite Australian Football players. Prognosis appears to be influenced by clinical factors, with CMSI sustained during running‐related activities and re‐injuries needing more time to recover.